2013
DOI: 10.1007/s10616-013-9575-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro genotoxic effects of ZnO nanomaterials in human peripheral lymphocytes

Abstract: In this study, possible genotoxic effects of zinc oxide (ZnO) nanoparticles were investigated in cultured human peripheral lymphocytes by using chromosome aberrations and micronucleus assays (MN). For this purpose, the cells were treated with ZnO (1, 2, 5, 10, 15 and 20 lg/mL) for 24 and 48 h. In this research, four types of chromosome aberrations were observed as chromatid and chromosome breaks, fragment and dicentric chromosomes. ZnO induced significant increase of the ratio of chromosomal aberrations as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…41 47 The previous studies reported that ZnO NPs induced DNA double-strand breaks frequency, olive tail moment, apoptosis, DNA breaks, and CA frequency on A549, HEK, HepG2, MEF Ogg1 +/+ , CHO, and human peripheral lymphocyte cells in the concentration range of 0.1 to 320 µg/mL. 23,48 52 Similarly, our findings also demonstrated that ZnO NPs caused genotoxicity on human lymphocytes in the concentration range of 12.5 to 250 ppm. The ZnO NPs also caused cell death at 500 to 2000 ppm dose range; therefore, no cells were counted at these concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…41 47 The previous studies reported that ZnO NPs induced DNA double-strand breaks frequency, olive tail moment, apoptosis, DNA breaks, and CA frequency on A549, HEK, HepG2, MEF Ogg1 +/+ , CHO, and human peripheral lymphocyte cells in the concentration range of 0.1 to 320 µg/mL. 23,48 52 Similarly, our findings also demonstrated that ZnO NPs caused genotoxicity on human lymphocytes in the concentration range of 12.5 to 250 ppm. The ZnO NPs also caused cell death at 500 to 2000 ppm dose range; therefore, no cells were counted at these concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…When investigated in cultured human peripheral lymphocytes, ZnO NPs significantly increased the MN frequency at concentrations of 10 and 15 g/mL compared with that in the control. However, lower concentrations (<10 g/mL) did not induce significant alterations in the MN frequency ( Gümüs et al, 2014). ZnO NPs and its bulky forms evaluated in human embryonic kidney (HEK293) and mouse embryonic fibroblast (NIH/3T3) cells were able to increase significantly the number of MNs at doses up 100 µg/mL (Demir et al, 2014).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 91%
“…The authors suggested that this could be due to an increased aggregation of ZnO NPs at high concentrations in the lymphocyte culture. Therefore, the addition of increasing concentrations/doses of ZnO NPs to lymphocyte cultures may not be paralleled by an equivalent increase in the genotoxic effects of this nanomaterial ( Gümüs et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Although selective cytotoxic effects on lymphocytes is an immunotoxic effect most frequently associated with immunosuppressive responses, a similar effect could be associated with implications for allergic conditions, as well (1121). Accordingly, metal nanomaterial cytotoxic and genotoxic effects have been investigated in murine and human lymphocytes in vitro and correlated to properties including size and morphology (1122)(1123)(1124)(1125)(1126)(1127)(1128). Interestingly, lymphocytes have been demonstrated to be more resistant to adverse effects of ZnONP compared to other immune cell types (1129).…”
Section: Metal Nanomaterials Effects On Processes Involved In Allergicmentioning
confidence: 99%